The qur’anic exegesis as a medium of Islamic education in Indonesia: A discourse analysis of tafsir Rahmat by H. Oemar Bakry - Nasrul Fatah; Syarifah Laili; Muhammad Hafiz Saleh; Hidayatullah Ismail (STAI Auliaurrasyidin Tembilahan, 2026)
Non-Indexed Publication